Peningkatan Pemahaman Siswa Pada Pembelajaran Akidah Akhlak Melalui Model Pembelajaran Kooperatif Mind Mapping - Hasan, Moch. Sya'roni; Rozaq, Abd.; Saifullah, Ragil (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
This study examines the implementation of the cooperative learning model, Mind Mapping, in enhancing students' understanding of the Akidah Akhlak subject in grade 10 science class 2 of MAN 6 Jombang. Employing a qualitative case study approach, this research involved 30 students and 5 Islamic Education teachers. Data was collected through participant observation, in-depth interviews, and document analysis. The results demonstrate that this learning model is effective in improving students' ability to interpret, conclude, and explain the material, as well as in addressing learning difficulties post-Distance Learning. The collaborative and visual aspects of this model contribute to increased student engagement and motivation, along with the development of non-academic skills. However, the research also identifies challenges in implementation, including differences in students' abilities and the need for more time. Although this model shows potential in integrating modern approaches with religious material, additional strategies are needed to develop students' higher-order thinking skills. This study concludes that the cooperative learning model, Mind Mapping, has significant potential in improving the quality of Akidah Akhlak learning, but requires further development for optimal implementation